Procurement Legislation and Performance of Constituency Development Fund Committees in Kenya - Muange, Eric; Chirchir, Dr. Michael (International Journal of Supply Chain Management, 2016)
Purpose: The purpose of the study was to determine the procurement legislation on performance of constituency development fund committees in Kenya. The research questions therefore were; to establish the effect of procurement legislation implementation on procurement performance in CDF Committees in Kenya; to determine the challenges facing the implementation of procurement legislation in CDF Committees in Kenya. Methodology: The study employed descriptive survey design. The population of the study was all the 290 constituencies and a census was conducted in the study. The study used primary data which was collected through use of a questionnaire. A five point likert scale questionnaire was used. Also a Yes or No structured questionnaire was also administered. The data collected was analyzed using descriptive statistics inferential statistics. The descriptive technique was used to generate frequencies, mean and percentages while inferential statistics were generated the fitness of the model and regression of coefficients. Results: The findings concluded that the procurement performance affected procurement legislation and procurement performance of constituency development fund (CDF) committees in Kenya. Effects of Procurement Legislation on procurement performance were found to be statistically significant with a positive impact on the importance of procurement performance. Results also indicate that Procurement management had positive and significant effect on procurement performance. The study recommends that a summarized regulatory framework for CDF procurement management be prepared by policy makers. Through legislation, the government should enact comprehensive laws to regulate procurement functions and outline clear policy and procedures to be followed by procurement entities as this will enhance accountability and transparency. Unique contribution to theory, practice and policy: The study also recommends that the government should employ professional auditors to undertake public procurement audit and facilitate their continuous training to ensure they are well equipped with necessary technical skills. These will ensure effectiveness of public procurement audit. The study also recommends that more public auditors be trained on public procurement audit and the CDF managers be exposed to audit as a positive management tool.